Folate receptor-positive circulating tumor cells predict survival and recurrence patterns in patients undergoing resection for pancreatic cancer - Cheng, Hao; Yang, Jun; Fu, Xu; Mao, Liang; Chu, Xuehui; Lu, Chenglin; Li, Gang; Qiu, Yudong; He, Wei (Frontiers in Oncology, 2022)
Objective: To evaluate the prognostic impact of folate receptor (FR)-positive circulating tumor cells (FR+ CTCs) for patients with pancreatic cancer (PC). Background: Risk stratification before surgery for PC patients remains challenging as there are no reliable prognostic markers currently. FR+ CTCs, detected by ligand-targeted polymerase chain reaction (LT-PCR), have shown excellent diagnostic value for PC in our previous study and prognostic value in a variety of cancer types. Methods: Peripheral blood samples from 44 consecutive patients diagnosed with PC were analyzed for FR+ CTCs. 25 patients underwent tumor resection and were assigned to the surgical group. 19 patients failed to undergo radical resection because of local advance or distant metastasis and were assigned to the non-surgical group. The impact of CTCs on relapse and survival were explored. Results: For the prognostic stratification, the optimal cut-off value of CTCs analyzed by receiver operating characteristic (ROC) curve was 14.49 folate units (FU)/3 ml. High CTC levels (> 14.49 FU/3 ml) were detected in 52.0% (13/25) of the patients in the surgical group and 63.2% (12/19) in the non-surgical group. In the surgical group, median disease-free survival (DFS) for patients with high CTC levels versus low CTC levels (< 14.49 FU/3 ml) was 8.0 versus 26.0 months (P = 0.008). In multivariable analysis, CTCs were an independent risk factor for DFS (HR: 4.589, P = 0.012). Concerning the recurrence patterns, patients with high CTC levels showed a significantly frequent rate of distant and early recurrence (P = 0.017 and P = 0.011). CTC levels remained an independent predictor for both distant (OR: 8.375, P = 0.014) and early recurrence (OR: 8.412, P = 0.013) confirmed by multivariable logistic regression. However, CTCs did not predict survival in the non-surgical group (P = 0.220). Conclusion: FR+ CTCs in resected PC patients could predict impaired survival and recurrence patterns after surgery. Preoperative CTC levels detected by LT-PCR may help guide treatment strategies and further studies in a larger cohort are warranted.